Mechanical strain induces a pro-fibrotic phenotype in human mitral valvular interstitial cells through RhoC/ROCK/MRTF-A and Erk1/2 signaling pathways. (October 2019) - Blomme, Benoit; Deroanne, Christophe; Hulin, Alexia; Lambert, Charles; Defraigne, Jean-Olivier; Nusgens, Betty; Radermecker, Marc; Colige, Alain
Abstract: The mitral valve is a complex multilayered structure populated by fibroblast-like cells, valvular interstitial cells (VIC) which are embedded in an extracellular matrix (ECM) scaffold and are submitted to the mechanical deformations affecting valve at each heartbeat, for an average of 40 million times per year. Myxomatous mitral valve (MMV) is the most frequent heart valve disease characterized by disruption of several valvular structures due to alterations of their ECM preventing the complete closure of the valve resulting in symptoms of prolapse and regurgitation. VIC and their ECM exhibit reciprocal dynamic processes between the mechanical signals issued from the ECM and the modulation of VIC phenotype responsible for ECM homeostasis of the valve. Abnormal perception and responsiveness of VIC to mechanical stress may induce an inappropriate adaptative remodeling of the valve progressively leading to MMV. To investigate the response of human VIC to mechanical strain and identify the molecular mechanisms of mechano-transduction in these cells, a cyclic equibiaxial elongation of 14% at the cardiac frequency of 1.16 Hz was applied to VIC by using a Flexercell-4000 T™ apparatus for increasing time (from 1 h to 8 h). We showed that cyclic stretch induces an early (1 h) and transient over-expression of TGFβ2 and αSMA. CTGF, a profibrotic growth factor promoting the synthesis of ECM components, was strongly induced after 1 and 2 h of stretching and still upregulated at 8 h. The mechanical stress-induced CTGF up-regulation was dependent on RhoC, but not RhoA, as demonstrated by siRNA-mediated silencing approaches, and further supported by evidencing RhoC activation upon cell stretching and suppression of cell response by pharmacological inhibition of the effector ROCK1/2. It was also dependent on the MEK/Erk1/2 pathway which was activated by mechanical stress independently of RhoC and ROCK. Finally, mechanical stretching induced the nuclear translocation of myocardin related transcription factor-A (MRTF-A) which forms a transcriptional complex with SRF to promote the expression of target genes, notably CTGF. Treatment of stretched cultures with inhibitors of the identified pathways (ROCK1/2, MEK/Erk1/2, MRTF-A translocation) blocked CTGF overexpression and abrogated the increased MRTF-A nuclear translocation. CTGF is up-regulated in many pathological processes involving mechanically challenged organs, promotes ECM accumulation and is considered as a hallmark of fibrotic diseases. Pharmacological targeting of MRTF-A by newly developed inhibitors may represent a relevant therapy for MMV. Graphical abstract: Unlabelled Image Highlights: Mechanical stress activates RhoC promoting, via ROCK, pro-fibrotic genes expression. Mechanical stress also activates MEK/Erk1/2, independently of RhoC and ROCK. MRTFA translocates to the nucleus, a process dependent on RhoC and Erk1/2 activation. Nuclear MRTFA associates with SRF to activate the transcription of pro-fibrotic genes.